Short- and Long-Term Consequences of Serious Parental Health Shocks - Ida Lykke Kristiansen (University of Copenhagen, Department of Economics, Center for Economic Behavior and Inequality (CEBI), 2020)
I show that serious, yet common, parental health shocks in childhood have immediate and lasting effects on mental health and human capital formation for children. Children who experience a parental health shock are more likely to have therapy and take anti-depressant medication following the shock. These children have lower test scores and school enrollment rates. The effect occurs immediately following the shock and persists at least into early adulthood. I find that the effect on test scores is no different for children in high- and lowincome families, but the families react differently to the shock; children from low-income families are more likely to be prescribed anti-depressants following the shock, while children from high-income families are more likely to have therapy. In addition, I find suggestive evidence that children who take anti-depressants following a parental health shock have lower educational attainments in early adulthood, while therapy doesn't have harmful long-term effects.
Keywords: I10; I14; I20; I24; 330; Parental health shocks; Parental death; Mental health; Education